DEMOGRAPHIC FACTORS AFFECTS THERAPEUTIC COMPLIANCE OF PATIENTS WITH CHRONIC MYELOCYTIC LEUKEMIA IN SURABAYA - Puspitadewi, Selly Andriani; Muliono, Ari Christy; Dewi, Bernadette Dian Novita (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: Leukemia is a hematologic malignancy that can affect all ages. In 2018, the death rate of leukemia in Indonesia reached 11,314 people. Imatinib is the first-line treatment for chronic myelocytic leukemia, which works by inhibiting the tyrosine kinase in the oncoprotein BCR-ABL. In Indonesia, the drug is the preferred therapy provided in hospitals and covered by the Social Security Administrator (BPJS). The side effects of these drugs are different from person to person, such as nausea, vomiting, headaches, indigestion, and joint pain. Compliance with taking medication is a determinant in the success of therapy, but several factors that influence compliance include age, gender, education level, and total income each monthPurpose: To compare the demographic factors that affect patients with chronic myelocytic leukemia in taking drugs in the Gist and Leukemia Community Surabaya.Method: This study used a Cross-Sectional Analytic research design. This research was conducted in September-November 2020 at the Gist and Leukemia Community Surabaya. The Gist and Leukemia Community in Surabaya is a community formed for sufferers of Chronic Myelocytic Leukemia and Gist (Tumors in the Stomach). The sample size required in the study, according to the Slovin formula, is 67 respondents. The sampling technique in this study is non-probability sampling so that this figure is met. Retrieval of patient demographic data and filling out the MMAS-8 questionnaire was done by filling in the form provided by the researcher in the form of a link on the google form. After that, short structured interviews were conducted with several respondents by telephone.Result: Based on the research that has been conducted, the results obtained are 67 respondents with high levels of compliance as many as 28 respondents, 22 respondents with moderate compliance, and 17 respondents with low compliance. With the number of male sex more than female, namely 40 men and 27 women. In addition, 20 respondents were aged 50-60 years, 22 respondents were aged 40-49 years old, 17 respondents were aged 30-39 years old, and eight respondents were aged 20-29 years old. In this study, the results obtained were 28 respondents with education levels of D3 / S1 / S2 / S3, 25 respondents with education levels of high school students, and 14 respondents with education levels of junior high school students. Also obtained the results of respondents with a monthly income of less than Rp 4,200,000 more, namely as many as 44 people compared to respondents with a monthly income, more than Rp 4,200,000 as many as 23 people. After obtaining the research data, the results of hypothesis testing using the Chi-Square test with sig. p <0.05. Results sig. p <0.05 means that the variable affects medication compliance in the respondent during sig. p> 0.05 means that the variable does not affect medication compliance among respondents. The results show that the factor influencing medication compliance in patients with chronic myelocytic leukemia is the monthly income with a sig. 0.025. Meanwhile, other factors such as gender, age, and education level do not affect medication compliance in patients with chronic myelocytic leukemia with sig. > 0.05.Conclusion: In the research that has been conducted with a total of 67 respondents, it can be concluded that Chronic Myelocytic Leukemia patients who are members of the Surabaya Gist and Leukemia Community for the period September-November 2020 are still in the category of obedience in consuming Imatinib drugs. The demographic factor that affects respondents' compliance with medication is the amount of income per month.